PENGEMBANGAN MODEL SUPERVISI AKADEMIK DENGAN PEMANFAATAN PLATFORM DIGITAL UNTUK MENINGKATKAN KOMPETENSI LITERASI DIGITAL GURU SD - Henri Prayogo; Sitti Hartinah; Dewi Apriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Digital transformation demands that teachers possess digital literacy competencies to create relevant and innovative learning experiences. However, in the Supervision Region IV of Comal Subdistrict, Pemalang Regency, these competencies remain low. Existing academic supervision practices are conventional and have yet to effectively address teachers' technological needs. This study aims to develop a coaching-based academic supervision model supported by digital platforms to enhance elementary school teachers’ digital literacy. The research uses a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate). The study involved elementary school teachers as research subjects, using questionnaires, interviews, observations, and documentation as instruments. The findings reveal that: (1) teachers require a more flexible supervision model that supports digital literacy enhancement; (2) the TIRTA coaching model supported by digital platforms (e.g., Zoom/Google Meet) was successfully designed to meet these needs; (3) the feasibility test confirmed the model's validity and practicality for implementation; and (4) the model effectively improved teacher competencies in the four pillars of digital literacy: digital skills, digital ethics, digital safety, and digital culture. This study recommends the implementation of coaching-based academic supervision supported by digital platforms as a strategic approach to developing teacher competencies in the digital era and strengthening the principal’s role as a transformational leader.